2022
DOI: 10.3390/ijms23042392
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of SARS-CoV-2 3CLPro Peptidomimetic Inhibitors through the Catalytic Dyad Histidine-Specific Protein–Ligand Interactions

Abstract: As the etiological agent for the coronavirus disease 2019, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) challenges the ongoing efforts of vaccine development and drug design. Due to the accumulating cases of breakthrough infections, there are urgent needs for broad-spectrum antiviral medicines. Here, we designed and examined five new tetrapeptidomimetic anti-SARS-CoV-2 inhibitors targeting the 3C-Like protease (3CLPro), which is highly conserved among coronaviruses and essential for viral repli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Moreover, five tetrapeptidomimetic anti‐3CL pro inhibitors, similar to the backbone of 13a , were successfully involved in the design of the catalytic dyad histidine residue (His41) of 3CL pro . Among them, TPM16 and TPM19 exhibited nanomolar inhibition and attenuated the cellular viral loads of SARS‐CoV‐2 114 . Compound 15l with novel α‐acyloxymethylketone warhead mimetic compounds was described by Bai et al., 94 which was identified to have potent SARS‐CoV‐2 3CL pro and viral replication inhibition in vitro.…”
Section: Synthetic Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, five tetrapeptidomimetic anti‐3CL pro inhibitors, similar to the backbone of 13a , were successfully involved in the design of the catalytic dyad histidine residue (His41) of 3CL pro . Among them, TPM16 and TPM19 exhibited nanomolar inhibition and attenuated the cellular viral loads of SARS‐CoV‐2 114 . Compound 15l with novel α‐acyloxymethylketone warhead mimetic compounds was described by Bai et al., 94 which was identified to have potent SARS‐CoV‐2 3CL pro and viral replication inhibition in vitro.…”
Section: Synthetic Compoundsmentioning
confidence: 99%
“…Among them, TPM16 and TPM19 exhibited nanomolar inhibition and attenuated the cellular viral loads of SARS-CoV-2. 114 Compound 15l with novel α-acyloxymethylketone warhead mimetic compounds was described by Bai et al, 94 which was identified to have potent SARS-CoV-2 3CL pro and viral replication inhibition in vitro. Moreover, co-crystallization of 15l with SARS-CoV-2 3CL pro confirmed the formation of covalent adducts.…”
Section: Peptidomimetic Sars-cov-2 3cl Pro Inhibitorsmentioning
confidence: 99%
“…Homologs are similar proteins found in different species, and the presence of human homologs of 3CLpro could increase the risk of adverse effects during administration in humans. By employing the Basic Local Alignment Search Tool (BLASTP) and Position-Specific Iterated BLAST (PSIBLAST) tools on the National Center for Biotechnology Information (NCBI, https://www.ncbi.nlm.nih.gov/, accessed on 20 May 2024), considering the sequence of 3CLpro from SARS-CoV-2 (PDB ID 7WOF) [31], we examined the sequence of 3CLpro from SARS-CoV-2 and restricted the search only to Homo sapiens (taxid:9606). Although we did not find human proteins with sequence similarity to 3CLpro of SARS-CoV-2, it is possible that some human proteins share structural similarities.…”
Section: -Chymotrypsin-like Protease: a Validated Molecular Targetmentioning
confidence: 99%
“…Table S3: Tabular representation of conventional hydrogen bonding and its bond length for top-ranked protein-ligand complexes. Table S4: Selection of top-ranked SARS-CoV-2 infection-causing ten key proteins/proteases identified by the literature review of 57 articles [1][2][3][4][5][6]44,.…”
Section: Supplementary Materialsmentioning
confidence: 99%